PENINGKATAN KAPASITAS GURU BERBASIS MANAJEMEN KURIKULUM DI KABUPATEN KEPULAUAN ARU - Rudolf Kempa; Desembra Sohilait; Asep Asep (German für Gesellschaft (J-Gefüge), 2023)
Curriculum management through capacity building of school principals and teachers in schools is an important part of improving the quality and quality of learning and learning programs. Through community service activities this was carried out at SMP Negeri 1 Aru Islands Regency. This service activity is carried out through several stages, namely planning, implementing, training and program development. Through this community service activity 1. Counseling related to curriculum planning which is part of this activity has begun to show a picture of what kind of planning will be carried out in the future. 2 The support of the school principal and teacher enthusiasm in planning, implementing, and evaluating learning is guided by the curriculum and learning development through design planning from the presenter